2019
DOI: 10.1021/acs.chemmater.8b03669
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur Poisoning Recovery on a Solid Oxide Fuel Cell Anode Material through Reversible Segregation of Nickel

Abstract: The p erovskite-type mixed oxide La 0.3 Sr 0.55 Ti 0.95 Ni 0.05 O 3−δ (LSTN) is demonstrated to exhibit the remarkable property of structural regeneration, where Ni can be reversibly exsoluted from the host perovskite lattice resulting in a regenerable Ni catalyst for solid oxide fuel cell anode applications. Results of catalytic tests for the water gas shift reaction and electrochemical investigations on a buttonsized fuel cell demonstrate the redox stability of LSTN, its potential application in solid oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 62 publications
0
47
0
Order By: Relevance
“…To further test the appropriateness of the transmission line model, a sulfur poisoning experiment was conducted by adding 10 ppm H 2 S to the feed gas. H 2 S is well‐known in literature to have a detrimental effect on the H 2 oxidation kinetics of Ni/YSZ based SOFC anodes , , , . The physical effect behind H 2 S poisoning is discussed to be related to blocking of hydrogen adsorption sites on Ni leading to a decreased reaction rate at the TPB.…”
Section: Resultsmentioning
confidence: 99%
“…To further test the appropriateness of the transmission line model, a sulfur poisoning experiment was conducted by adding 10 ppm H 2 S to the feed gas. H 2 S is well‐known in literature to have a detrimental effect on the H 2 oxidation kinetics of Ni/YSZ based SOFC anodes , , , . The physical effect behind H 2 S poisoning is discussed to be related to blocking of hydrogen adsorption sites on Ni leading to a decreased reaction rate at the TPB.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction feature of NiO (ca. 370 °C) disappears after reoxidation at Treox ≥ 800 °C, thus indicating successful and complete Ni reincorporation at this temperature [2]. The initial TPR of calcined LSTFN-2Fe5Ni ( Figure 6b) was not as well defined as the one recorded for LSTN-5Ni.…”
Section: Sulfur Uptakementioning
confidence: 87%
“…In recent years perovskite-type metal oxide (PMO) derived metal catalysts have attracted great attention for their high redox stability, due to the reversible segregation of catalytically active metals from the bulk of the oxide in reducing atmospheres and their reincorporation during oxidative treatments [1]. It was demonstrated that this property allows for the regeneration of catalysts, which have suffered from active metal particle sintering, as well as the recovery of catalysts poisoned by coke or sulfur through simple redox cycling [2,3]. However, achieving catalyst stability while maintaining high catalytic conversion rates, thus decreasing the necessary frequency of catalyst regeneration cycles, appears to be as propitious as increasing catalyst regenerability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations